Local Economic Development through Corn Farming in Batui and Kintom Sub-Districts - Tija, Irmansyah; Febriyanti, Lailul; Alfiantiningtias, Widi; Yasin, Muhammad (Prospect Publishing, 2025)
Corn is one of the national strategic commodities, playing a crucial role in supporting food security and other industries. The demand for Corn is increasing due to the development of the food and animal feed industries. Although Corn production in 2024 experienced a surplus of 2.98%, there are still challenges in meeting domestic Corn needs. Fluctuating production, climate change, land degradation, and dependence on imports are major issues in Corn development. The government aims to produce 16.7 million tons of Corn by 2025 as part of its strategy to reduce imports and increase food self-sufficiency. In addition, the surge in demand for animal feed resulting from increased animal protein consumption is also driving the priority of developing this commodity. The Local Economic Development Program can be one of the supporting efforts in increasing Corn production as a strategy to fulfil food security. As a community empowerment program initiated by DSLNG, this program can reach three sub-districts in Banggai Regency: Batui, Nambo, and Kintom. One of the focuses of the Local Economic Development Program is to support the increase of local corn production, especially in the Kintom District. As a result of the assistance provided by the company, the corn harvest can reach 4,683 kg, equivalent to IDR 21,073,500, specifically in the Kintom Sub-district.